A mixed-methods feasibility study of a goal-focused manualised intervention to support people with dementia to stay living independently at home with support from family carers: NIDUS (New Interventions for Independence in Dementia Study) Family. (3rd August 2021) - Rapaport, Penny; Burton, Alexandra; Palomo, Marina; Griffiths, Jessica; Kelleher, Daniel; Leverton, Monica; Vickerstaff, Victoria; Barber, Julie; Bird, Megan; Budgett, Jessica; Birch, Jodie; Rockwood, Kenneth; et al.
Abstract: Objectives: To examine the feasibility and acceptability of NIDUS-Family, a 6–8 session manualised, individually tailored, modular intervention supporting independence at home for people with dementia; and explore participants' and facilitators' experiences of the intervention. Method: In this single group multi-site feasibility study, trained, supervised non-clinically qualified graduates (facilitators) delivered NIDUS-Family to family carer and people living with dementia dyads. We recruited participants from GP practices and memory services in London and Bradford. We completed quantitative outcomes pre- and post-intervention; and conducted qualitative interviews with participants and facilitators. Our pre-specified main outcomes were proportion of potential participants approached who agreed to participate, intervention adherence and acceptability to family carers, and facilitator fidelity to the manual. Results: We recruited 16 dyads (57% of those approached); 12 (75%) completed the intervention. Of 12 participants rating intervention acceptability, 9 (75%) agreed or strongly agreed that it had helped; 2 (18%) neither agreed nor disagreed and 1 (8%) disagreed. Mean facilitator fidelity was high (81.5%). Dyads set on average 3.9 goals; these most commonly related to getting out and about and increasing activity/hobby participation ( n  = 10); carer wellbeing ( n  = 6), managing physical complaints ( n  = 6); meal preparation/cooking ( n  = 5); and reducing irritability, frustration or aggression ( n  = 5). Almost all secondary outcomes changed in a direction indicating improvement. In our qualitative analysis we identified three overarching themes; relationships facilitate change, goal-focused versus manualised approach and balancing the needs of carers and people with dementia. Conclusion: NIDUS-Family was feasible and acceptable to participants. Following refinements, testing in a pragmatic trial is underway.